The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ijscr.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic retrieval of a sewing needle from the liver: A case report

Abstract: HighlightsIngested foreign bodies are a common presentation.Ingested foreign bodies can migrate/penetrate to the liver.Patients can present with symptoms including epigastric abdominal pain.In some cases hepatic foreign bodies can be extracted through a laparoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…About 2% of foreign bodies should be extracted through surgery. [13,14] Once a foreign body is stuck in the digestive tract, people in many regions of China tend to swallow the foreign body by swallowing steamed bread or rice and vegetable rolls. However, this method is not recommended as it may cause incarceration of the foreign body, aggravating the disease, and increasing treatment risk.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…About 2% of foreign bodies should be extracted through surgery. [13,14] Once a foreign body is stuck in the digestive tract, people in many regions of China tend to swallow the foreign body by swallowing steamed bread or rice and vegetable rolls. However, this method is not recommended as it may cause incarceration of the foreign body, aggravating the disease, and increasing treatment risk.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…Therefore, further investigations, such as ultrasound or CT scan, are usually needed. A CT scan is recommended as a routine examination before surgery [ 42 , 43 ]. In our review, seven out of 16 patients underwent a CT scan [ 2 , 4 , 16 , 17 , 18 , 19 , 20 ] preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported retrieval of sharp foreign bodies. 8,9 The young trainee surgeon should have acquired the skill of intra-corporeal suturing technique. He should have mastered the act, especially during laparoscopic cholecystectomy, appendicectomy, and the likes.…”
Section: Discussionmentioning
confidence: 99%